The homo zappiens and the use of televisual devices: potential impacts in the process of basic literacy building - Prioste, Claudia [UNESP] (Centro Univ La Salle-rj, 2017)
The access of Brazilian children to ICT (Information and Communication Technologies) has increased, however, there is still very few studies which analyze their possible impact in the basic literacy phase. Objective: to understand the domestic and scholar use of televisual devices of children from two public schools. Methodological aspects: action-research, whose data collection was performed through interviews with teacher and family groups, apart from participative observations in the information technology laboratory in two Elementary School I third year classes. Results: in the domestic environment, most children had the habit of watching soap operas and playing with and on the tablet of mobile phone. The families believed that this type of device jeopardize children's dedication to studies, associating them to irritability, stubbornness, low tolerance to frustration and lack of persistence. Such characteristics may be related to violent games and to the habit of zapping. However, it must be highlighted that the school has also made assumptions of what we call zap pedagogy, promoting activities in the pedagogical books or in the computer which favor zapping from one theme from another, jeopardizing the learning process. It may be concluded that the school should orient parents and children towards better use of televisual devices. In addition, it is necessary to promote actions aiming basic literacy that stimulate attention capability, memory and persistence, also using digital resources for this purpose.
Keywords: Basic literacy; Native digital; Information technologies in education; Homo zappiens